2001
DOI: 10.1002/1096-9071(200104)63:4<293::aid-jmv1004>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of seroresponses to double dose and booster influenza vaccination in frail elderly subjects

Abstract: Responses to influenza vaccination are poor in frail elderly subjects who suffer the greatest morbidity and mortality due to infection. Therefore, a randomized clinical trial was performed to determine the effect of a double dose and booster vaccination on antibody responses after influenza vaccination. A total of 815 patients (median age 83 years, median disability score 8, median disease categories 2 and median number of medications 4) residing in 14 nursing homes in the Netherlands were vaccinated during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Between 30-70% reach an HI titre of .1:40 [260][261][262][263]. In these age groups, a double dose, or a booster dose, has been shown to increase the geometric mean IgG antibody concentration by ,15% [264]. Live attenuated vaccines do not reach as high HI titres as the inctivated, but induce significantly higher local IgA titres in the nasal mucosa [258].…”
Section: Prevention By Vaccinationmentioning
confidence: 89%
“…Between 30-70% reach an HI titre of .1:40 [260][261][262][263]. In these age groups, a double dose, or a booster dose, has been shown to increase the geometric mean IgG antibody concentration by ,15% [264]. Live attenuated vaccines do not reach as high HI titres as the inctivated, but induce significantly higher local IgA titres in the nasal mucosa [258].…”
Section: Prevention By Vaccinationmentioning
confidence: 89%
“…Except for age, which was adjusted in our analyses, there was no significant difference in demographic and clinical profiles between frail and nonfrail participants. Of note, several studies evaluated TIV-induced antibody response and/or TIV efficacy in “frail” institutionalized older persons [4143]. However, despite a specific type of disability or disabilities that require long-term functional and healthcare support, many nursing home residents may not be truly frail and can still mount a robust antibody response to TIV immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also supports giving multiple doses of the vaccine. Although trials are limited in children, this has been shown in other settings to boost vaccine serologic responses [71,72].…”
Section: Influenza Vaccination For Children On Chemotherapymentioning
confidence: 98%